Answer:
(-3, 8)
Step-by-step explanation:
We are given two equations and we have to find the solution to the given equations. We can do this by using substitution method as shown below:
[tex]2x+y=2[/tex] Equation 1
[tex]x-3y=-27[/tex] Equation 2
From Equation 1, we can get the value of y as:
[tex]y=2-2x[/tex] Equation 3
Using this value of y in equation 2, we get:
[tex]x-3(2-2x)=-27\\\\ x-6+6x=-27\\\\ 7x=-21\\\\ x=-3[/tex]
Thus value of x is -3. Using this value in Equation 3, we get:
[tex]y=2-2(-3)\\\\ y=2+6\\\\ y=8[/tex]
Thus the solution to the given equations is (-3, 8)